Teachers’ Obstacles in Utilizing Information and Communication Technology - Muhammad Kristiawan; Muhaimin Muhaimin (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2019)
This study aims to study teacher barriers to utilizing information and communication media (ICT) for learning media. This research was carried out at Public Elementary School 24 Pulau Rimau located in Karang Manunggal village, Pulau Rimau sub-district, Banyuasin district. The subjects of this study were teachers at Public Elementary School 24 Pulau Rimau who tested 16 people. In conducting this research, data from certain sources are needed that are as expected in this study. The technique of collecting data is by observation and interview. Data were analyzed using percentages to see the percentage of respondents' answers. Furthermore, all data is processed by analyzing qualitative data, namely data reduction, data display, and data verification. The formulation of the problem in this study is what forms are questioned by the teacher in utilizing technology-based media in Public Elementary School 24 Pulau Rimau ? From the results of research on teacher barriers to using Information Technology (ICT) in Public Elementary School 24 Pulau Rimau, two aspects related to the ability of teachers and Information and Communication Technology (ICT) were inadequate. The obstacle of the teacher's ability to master ICT is that the teacher is not proficient in using computers, judging from the percentage of teacher answers, 75% say they are not proficient in using technology-based media, whereas using computers is one of the activities that support computer-based media. In addition, teachers do not have an advanced educational background in the use of ICT media. Another obstacle in terms of facilities, in Public Elementary School 24 Pulau Rimau there is no electricity network (PLN). In addition to not having a PLN, there is also the unavailability of computer facilities and laptops at the Public Elementary School 24 Pulau Rimau.